Lord Surya depicted on a wall - Temples of India Project Team (Jio Institute, 2024)
This sculpture is arguably the oldest at the shrine, dated by Ambika Dhaka to the 8th century CE The sculpture thus significantly precedes the Harshnath Temple, which was built in the second half of the 10th century. The Harshnath stone inscription records the devotion towards Lord Harsha by an early founding figure of the Chauhan line, Guvaka-I, a local chieftain and feudatory of the powerful imperial Pratihara dynasty, who lived roughly during the first quarter of the ninth century CE. The Shaiva association with the hill may have preceded the time of Guvaka, but what can be said with certainty is the much older association of the hill with Surya. The figure exhibits standard iconographic features of the Sun God, such as fully bloomed lotuses in two hands, a long tunic, boots and retinue figures in pairs like his companions - Danda and Pingala, his wives and his sons, Ashvins.